A cluster-randomized trial of client and provider directed financial interventions to align incentives with appropriate case management in private medicine retailers: Results of the TESTsmART trial in Lagos, Nigeria. - Theodoor Visser; Jeremiah Laktabai; Emmah Kimachas; Joseph Kipkoech; Diana Menya; David Arthur; Yunji Zhou; Tabitha Chepkwony; Lucy Abel; Emily Robie; Mark Amunga; George Ambani; et al. (Public Library of Science (PLoS), 2024)
Malaria remains a major health priority in Nigeria. Among children with fever who seek care, less than a quarter gets tested for malaria, leading to inappropriate use of the recommended treatment for malaria; Artemisinin-based Combination Therapy (ACT). Here we test an innovative strategy to target ACT subsidies to clients seeking care in Nigeria's private retail health sector who have a confirmed malaria diagnosis. We supported point-of-care malaria testing (mRDTs) in 48 Private Medicine Retailers (PMRs) in the city of Lagos, Nigeria and randomized them to two study arms; a control arm offering subsidized mRDT testing for USD $0.66, and an intervention arm where, in addition to access to subsidized testing as in the control arm, clients who received a positive mRDT at the PMR were eligible for a free (fully subsidized) first-line ACT and PMRs received USD $0.2 for every mRDT performed. Our primary outcome was the proportion of ACTs dispensed to individuals with a positive diagnostic test. Secondary outcomes included proportion of clients who were tested at the PMR and adherence to diagnostic test results. Overall, 23% of clients chose to test at the PMR. Test results seemed to inform treatment decisions and resulted in enhanced targeting of ACTs to confirmed malaria cases with only 26% of test-negative clients purchasing an ACT compared to 58% of untested clients. However, the intervention did not offer further improvements, compared to the control arm, in testing rates or dispensing of ACTs to test-positive clients. We found that ACT subsidies were not passed on to clients testing positive in the intervention arm. We conclude that mRDTs could reduce ACT overconsumption in Nigeria's private retail health sector, but PMR-oriented incentive structures are difficult to implement and may need to be complemented with interventions targeting clients of PMRs to increase test uptake and adherence. Trials registration: Clinical Trials Registration Number: NCT04428307. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7816435/ Correction: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC9476591/.